2019
DOI: 10.1073/pnas.1910510116
|View full text |Cite|
|
Sign up to set email alerts
|

Cognitive and noncognitive predictors of success

Abstract: When predicting success, how important are personal attributes other than cognitive ability? To address this question, we capitalized on a full decade of prospective, longitudinal data from n = 11,258 cadets entering training at the US Military Academy at West Point. Prior to training, cognitive ability was negatively correlated with both physical ability and grit. Cognitive ability emerged as the strongest predictor of academic and military grades, but noncognitive attributes were more prognostic of other ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
85
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 48 publications
(50 reference statements)
3
85
2
3
Order By: Relevance
“…Is it possible that the various processes thought to underlie and describe self-regulation (e.g., choosing the best means to achieve a goal; overcoming short-term temptations) are actually different aspects of intelligence? This departs from the way self-regulation has been discussed in the past; and we don't want to overstate things-trait studies have indicated that both cognitive and noncognitive factors are important (Duckworth et al, 2019). Nonetheless, we believe that the overlap between intelligence and self-regulation has been underemphasized, and we prescribe better integration of these concepts in the future.…”
Section: Cognitive Functioningmentioning
confidence: 84%
See 4 more Smart Citations
“…Is it possible that the various processes thought to underlie and describe self-regulation (e.g., choosing the best means to achieve a goal; overcoming short-term temptations) are actually different aspects of intelligence? This departs from the way self-regulation has been discussed in the past; and we don't want to overstate things-trait studies have indicated that both cognitive and noncognitive factors are important (Duckworth et al, 2019). Nonetheless, we believe that the overlap between intelligence and self-regulation has been underemphasized, and we prescribe better integration of these concepts in the future.…”
Section: Cognitive Functioningmentioning
confidence: 84%
“…At the trait level, there is a long history of examining and comparing trait measures of self-regulation (e.g., conscientiousness) and intelligence on various beneficial life outcomes, such as academic achievement, health, and occupational status (e.g., Chamorro-Premuzic & Furnham, 2008;Duckworth et al, 2019;Duckworth, Weir, Tsukayama, & Kwok, 2012). From these analyses, two themes emerge.…”
Section: Role Of Cognitive Functioningmentioning
confidence: 99%
See 3 more Smart Citations